2019
DOI: 10.1002/ange.201902908
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Total Synthesis of (−)‐Himalensine A

Abstract: The daphniphyllum alkaloids are a structurally fascinating and remarkably diverse family of natural products. General strategies for the chemical synthesis of their challenging architectures are highly desirable for efficiently accessing these intriguing alkaloids and addressing their pharmaceutical potential. Herein, a concise strategy designed to provide general and diversifiable access to various daphniphyllum alkaloids is described and utilized in the asymmetric synthesis of (−)‐himalensine A, which was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 118 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Compounds 40 and 41 did not need to be isolated, as basic hydrolysis of the thioester motif in the same pot successfully produced dapholdhamine B (1, 80%). As an authentic sample of natural 1 was not available, comparing the 1 H and 13 C NMR data of the natural product with our synthetic sample was difficult because the NMR chemical shifts of our synthetic amino acid were extremely pH-sensitive (see the Supporting Information). Consequently, a small amount of synthetic 1 was treated with HCl to quantitatively give dapholdhamine B lactone (42).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 40 and 41 did not need to be isolated, as basic hydrolysis of the thioester motif in the same pot successfully produced dapholdhamine B (1, 80%). As an authentic sample of natural 1 was not available, comparing the 1 H and 13 C NMR data of the natural product with our synthetic sample was difficult because the NMR chemical shifts of our synthetic amino acid were extremely pH-sensitive (see the Supporting Information). Consequently, a small amount of synthetic 1 was treated with HCl to quantitatively give dapholdhamine B lactone (42).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 Highly challenging and congested polycyclic ring systems, along with promising bioactivities, make these alkaloids intriguing synthetic targets. 1b−d,3 Since Heathcock's pioneering syntheses of methyl homodaphniphyllate 4a,b and codaphniphylline 4c (daphniphylline-type), methyl homosecodaphniphyllate 4d and secodaphniphylline 4e (secodaphniphylline-type), bukittinggine 4f (bukittinggine-type), and daphnilactone A 4g (daphnilactone A-type), many impressive total syntheses of various Daphniphyllum alkaloids have been reported by the groups of Carreira 5 (daphmanidin E; daphmanidin A-type), Smith 6 (calyciphylline N; daphmanidin A-type), Li 7 (daphenylline, 7a,b daphnilongeranin B, 7c daphnipaxianine A, 7b daphniyunnine E, 7c dehydrodaphnilongeranin B, 7c hybridaphniphylline B, 7c himalenine D, 7b and longeracinphyllin A; 7d calyciphylline A-type), Hanessian 8 (isodaphlongamine H; a putative member of calyciphylline B-type alkaloids), Fukuyama 9 (daphenylline; calyciphylline A-type), Zhai 10 (daphenylline and daphnilongeranin B; calyciphylline A-type), Dixon 11 (himalensine A; calyciphylline A-type), Qiu 12 (daphenylline; calyciphylline A-type), ourselves 13 (himalensine A; calyciphylline A-type), Gao 14 (himalensine A; calyciphylline A-type), and Sarpong 15 (daphlongamine H and isodaphlongamine H; calyciphylline B-type) (Figure 1). Dapholdhamine B (1, Figures 1 and 2) belongs to the unexplored daphnezomine A-type subfamily and was isolated and structurally assigned in 2009 by Hao et al 16 The chemical structure of dapholdhamine B contains a rare aza-adamantane core skeleton and eight contiguous stereocenters, including three contiguous fully substituted stereocenters, which present a daunting synthetic challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Synthesis of the complex azapolycyclic architectures of Daphniphyllum alkaloids have attracted considerable attention, and various methods have been developed to improve synthetic efficiency and scalability. Elegant total syntheses of Daphniphyllum alkaloids have been described by the groups of Heathcock, Carreira, Smith, Fukuyama, Hanessian, Li, Zhai, Dixon, Qiu, and Xu which have enabled promising downstream syntheses and mechanistic studies of natural alkaloids.…”
mentioning
confidence: 99%
“…[210] It was isolated from Nepalese Daphniphyllum himalense by Yue et al in 2016. [211] In 2019 Xu et al [212] reported a concise method to make common admittance to different Daphniphyllum alkaloids and used in the asymmetric synthesis of (À )-himalensine A, which was performed in 14 steps.…”
Section: Cu (Ii) Saltsmentioning
confidence: 99%